The association between serum ferritin levels and growth parameters in children with β-thalassemia major - Heru Noviat Herdata; Veria Taufani; Eka Destiani; Rusdi Andid (AcTion: Aceh Nutrition Journal, 2025)
Beta-thalassemia major requires regular blood transfusions, which can result in iron overload. Excess iron disrupts bone homeostasis by inhibiting osteoblast activity and stimulating osteoclast differentiation via elevated receptor activator of nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) levels, thereby increasing the risk of osteoporosis. This may lead to vertebral compression, fractures, and reduced heights. This study aimed to assess the correlation between serum ferritin concentration and linear growth parameters (height and sitting height) in adolescents with beta-thalassemia major. An observational analytical study was conducted at the Thalassemia Center of Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia, from July to August 2023 using secondary data from medical records. The study included 40 participants (21 females) who received ≥10 blood transfusions. Anthropometric measurements were assessed using WHO Reference 2007. Data were analyzed using Pearson's correlation tests. Results, most participants had serum ferritin levels >2000 ng/mL (72,5%), extremely short stature (82,5%), and abnormal sitting height (57,5%). A weak but statistically significant negative correlation was observed between serum ferritin levels and height (r = -0,165; p = 0,030) and sitting height (r = -0,150; p = 0,035). In conclusion, although the correlation is weak, elevated ferritin levels may contribute to impaired linear and spinal growth in adolescents with β-thalassemia major.